The Relationship Between Stress Levels And Smoking Intensity Among College Students - Cindi Kezia Simbolon (Journal of Education Psychology and Social Development, 2025)
Smoking relationship between stress levels and smoking intensity among students at State University of Medan. A quantitative cross-sectional survey was conducted involving 32 student smokers selected using stratified random sampling. Stress was measured using the Perceived Stress Scale (PSS), while smoking intensity was assessed through a structured questionnaire capturing frequency and related dependency patterns. Data were analyzed using descriptive statistics and Pearson Product–Moment correlation. Results showed a weak positive correlation between stress and smoking intensity (r = 0.271), indicating that higher stress tended to be followed by higher smoking intensity. However, the association was not statistically significant (p = 0.133), suggesting that stress alone does not among university students remains a public health concern and is frequently associated with academic and psychological demands. In Indonesia, where tobacco consumption is high, students may adopt smoking as a coping response to stress, yet empirical evidence on how stress relates to smoking intensity is still mixed. This study examined the adequately explain variations in smoking intensity in this sample. This finding implies that smoking intensity among students is likely shaped by multifactor influences, including peer exposure, social norms, self-efficacy, and contextual environmental factors, which may attenuate or override the direct role of stress. Therefore, campus-based interventions should integrate stress management with broader strategies targeting social and environmental determinants of smoking behavior. Further studies with larger samples and models testing mediating and moderating mechanisms are recommended.